ANALISIS PENDIDIKAN KARAKTERISTIK AKHLAK ANAK USIA SD/MI DI ERA SOCIETY 5.0 - Indriani; Astrid Putri Pratiwi; Jauhara; Lailatul Mukjizat; Siti Fatimah (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2023)
Efforts to instill good, noble behavior in children are character education in early childhood. The environment in which the child is located can be part of the child's character education. The family is the first environment for children so that parents and families have the responsibility to teach good attitudes to children. Children need guidance from adults, both parents and teachers. Character itself is defined as morals, manners, character or behavior that becomes a habit. Early age is a critical period in individual development so that character education is needed from an early age. Society 5.0 provides an example of how data can be used to mobilize and connect things, including solving social problems. In the era of society 5.0, humans are required to have more abilities in solving complex problems, being creative and thinking critically. This study aims to find out and provide an overview that moral and religious education is very important for children in facing the era of society 5.0. Educational transformation has developed rapidly, along with increasingly developing technology making systems, learning methods, technology and other things change including the character of students. Character education must also be built together by the family, school, and the environment. School is a place that is considered appropriate for the process of forming character education in students. The impact of social character education in the era of society 5.0 on the behavior of elementary school children is as explained that character education is a systematic intentional effort to develop virtues that have a positive impact on both the individual and the social environment and the process is not instantaneous, but through habituation efforts. In preparing for the challenges of the society 5.0 era, the educational curriculum design mentions several substantive points, namely character education, having the ability to think critically and innovatively, and being able to apply technology in the era of society 5.0. seeing how technological developments can affect a person's life, it is necessary to cultivate character, especially in early childhood. Regarding how the education of the moral characteristics of children in that era, this article will contain "Analysis of the educational moral characteristics of elementary school-aged children in the era of society 5.0".